CALORIMETRIC STUDY OF PEROVSKITE SOLID SOLUTIONS IN THE CASIO3-CAGEO3 SYSTEM - Kojitani H.; Navrotsky A.; Akaogi M. (My University, 2001)
Enthalpies of drop solution (ΔH drop-sol) of CaGeO3, Ca(Si0.1Ge0.9)O3, Ca(Si0.2Ge0.8)O3, Ca(Si0.3Ge0.7)O3 perovskite solid solutions and CaSiO3 wollastonite were measured by high-temperature calorimetry using molten 2PbO · B2O3 solvent at 974 K. The obtained values were extrapolated linearly to the CaSiO3 end member to give ΔH drop-sol of CaSiO3 perovskite of 0.2 ± 4.4 kJ mol−1. The difference in ΔH drop-sol between CaSiO3, wollastonite, and perovskite gives a transformation enthalpy (wo → pv) of 104.4 ± 4.4 kJ mol−1. The formation enthalpy of CaSiO3 perovskite was determined as 14.8 ± 4.4 kJ mol−1 from lime + quartz or −22.2 ± 4.5 kJ mol−1 from lime + stishovite. A comparison of lattice energies among A2+B4+O3 perovskites suggests that amorphization during decompression may be due to the destabilizing effect on CaSiO3 perovskite from a large nonelectrostatic energy (repulsion energy) at atmospheric pressure. By using the formation enthalpy for CaSiO3 perovskite, phase boundaries between β-Ca2SiO4 + CaSi2O5 and CaSiO3 perovskite were calculated thermodynamically utilizing two different reference points [where ΔG(P,T )=0] as the measured phase boundary. The calculations suggest that the phase equilibrium boundary occurs between 11.5 and 12.5 GPa around 1500 K. Its slope is still not well constrained.
Keywords: PEROVSKITE; CASIO3; CAGEO3; CALORIMETRY; HIGH-PRESSURE PHASE TRANSITION